POLYPHONIC FEMINISM: INTERSECTIONALITY AND THE MULTIPLICITY OF WOMEN’S VOICES IN BERNARDINE EVARISTO’S GIRL, WOMAN, OTHER - Hlail, Mohanad Abdulkadhim (Journal of Higher Education and Academic Advancement, 2025)
Objective: This article explores Bernardino Evaristo’s girl, woman, and other as a literary statement of intersectional feminism. It focuses on the polyphonic structure used by the novelist and how challenges monolithic exemplification of womanhood. Despite of receiving considerable critical acclaim for its variety, less interest has been given by scholars to the interplay between feminist politics and narrative form. Method: This article deals with that gap by analyzing how the multiplicity of voices through the novel presents complicated intersection of class, generational history, sexuality and race, especially within the framework of black British women’s competences and experiences. The research utilizes close textual analysis of the twelve correlated narratives to examine how the writer creates her feminist version; that is totally based on Kimberle Crenshaw’s theory of intersectionality as well as the concept of polyphony by Mikhail Bakhtin. Results: The outcomes suggest that stylistic choice functions as less than polyphony. It becomes a way to intensify marginalized perspectives stand against the patriarchal and cultural elimination. Novelty: This study helps to show how formal novelty in literature can draw political and cultural critique.